A new species of Platypleura Amyot & Audinet-Serville, 1843 (Hemiptera: Cicadidae: Cicadinae) from the Eastern Ghats of Andhra Pradesh, India - Marathe, Kiran; Yeshwanth, H. M.; Basu, Dipendra Nath; Kunte, Krushnamegh (Zootaxa, 2017)
We here describe a new cicada species, Platypleura poorvachala sp. nov., (Hemiptera: Cicadidae: Cicadinae) from the Eastern Ghats of India. The combination of following characters distinguishes this species from its platypleurine relatives: (a) transverse continuous infuscation along the nodal line and in the central area of the forewings, and (b) opaque hindwings, which are indochine-coloured with two prominent sub-distal black bands. We illustrate the male and female types and the male genitalia, and present a photographic plate for comparison of this species with other Indian and Southeast Asian Platypleura species with respect to its morphology and distribution.